2019
DOI: 10.1136/bcr-2019-229423
|View full text |Cite
|
Sign up to set email alerts
|

Epistaxis and gross haematuria with severe thrombocytopaenia associated with influenza vaccination

Abstract: Epistaxis may be attributed to many causes during the winter including dry mucous membranes from low indoor humidity from heating. However, epistaxis may also be due to thrombocytopaenia. Immune thrombocytopaenia purpura (ITP) is an autoimmune disorder causing thrombocytopaenia. Viral infections sometimes lead to ITP. Vaccines, predominantly the measles-mumps-rubella vaccine, have been associated with the development of ITP. There are several published case reports regarding influenza vaccine induced ITP. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Immune-complexes of antibodies against influenza virus are also capable of activating platelets through an interaction with the Fc-ϒIIA receptor present on the platelet surface, leading to thrombocytopenia in a humanized mouse model. These findings, combined with reported influenza vaccine induced ITP, point to a link between influenza virus-specific adaptive immunity and thrombocytopenia [ 193 , 194 , 195 ].…”
Section: Resultsmentioning
confidence: 76%
“…Immune-complexes of antibodies against influenza virus are also capable of activating platelets through an interaction with the Fc-ϒIIA receptor present on the platelet surface, leading to thrombocytopenia in a humanized mouse model. These findings, combined with reported influenza vaccine induced ITP, point to a link between influenza virus-specific adaptive immunity and thrombocytopenia [ 193 , 194 , 195 ].…”
Section: Resultsmentioning
confidence: 76%
“…It is critical to underscore that ITP following the influenza vaccine is rare: per the Vaccine Adverse Events Reporting System (VAERS) database [6], there were only 133 cases reported between 1990 and early 2022 in the United States [6]; additionally, there are only a handful of case reports in the literature [7][8][9][10][11][12][13][14]. These reports largely document experiences similar to our own, specifically about onset (the condition typically develops about four to seven days following vaccination).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether viral infection, lymphocyte count at first diagnosis, antiplatelet antibody, megakaryocyte count and other factors are related to prognosis, there are currently different opinions in domestic and foreign research. [28][29][30][31] The newly diagnosed ALC is related to the immunity of the child. Lyu et al 32 showed that the absolute value of newly diagnosed lymphocytes is an independent factor leading to chronic ITP in children.…”
Section: Discussionmentioning
confidence: 99%